2021
DOI: 10.3389/fmolb.2021.743403
|View full text |Cite
|
Sign up to set email alerts
|

In the Model Cell Lines of Moderately and Poorly Differentiated Endometrial Carcinoma, Estrogens Can Be Formed via the Sulfatase Pathway

Abstract: Endometrial cancer (EC) is the most common gynecological malignancy in resource-abundant countries. The majority of EC cases are estrogen dependent but the mechanisms of estrogen biosynthesis and oxidative metabolism and estrogen action are not completely understood. Here, we evaluated formation of estrogens in models of moderately and poorly differentiated EC: RL95-2 and KLE cells, respectively. Results revealed high expression of estrone-sulfate (E1-S) transporters (SLCO1A2, SLCO1B3, SLCO1C1, SLCO3A1, SLC10A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The expressions of the genes of interest ( Table 1 ) were examined by quantitative PCR (qPCR) using the TaqMan ® Fast Advanced Master Mix (Applied Biosystems; Foster City, CA, USA) or SYBR Green I Master (Roche, Basel, Switzerland) as described in our previous studies [ 20 ]. Quantification was accomplished with the Applied Biosystems ® ViiA TM 7 Real-Time PCR System (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expressions of the genes of interest ( Table 1 ) were examined by quantitative PCR (qPCR) using the TaqMan ® Fast Advanced Master Mix (Applied Biosystems; Foster City, CA, USA) or SYBR Green I Master (Roche, Basel, Switzerland) as described in our previous studies [ 20 ]. Quantification was accomplished with the Applied Biosystems ® ViiA TM 7 Real-Time PCR System (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…E1-S metabolism in the cell lines was assessed using LC-MS/MS, which comprised a Shimadzu Nexera XR system (Shimadzu Corporation, Kyoto, Japan) and a triple quadruple MS system (Triple Quad 3 500; AB Sciex Deutchland GmbH, Darmstadt, Germany). The levels of E1-S, E1, E2, and E2-sulfate (E2-S) were assessed with the LC-MS/MS method as described previously [ 20 ]. Briefly, a deuterated internal standard of E2-d2 was added to the cell culture medium samples, and the lipophilic fraction containing the analytes of interest was extracted with solid-phase extraction (Strata-X polymer-based columns; Phenomenex, Torrance, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogens can significantly promote ovarian cancer development stimulating ovarian surface epithelial cells proliferation and invasiveness [21] since both nuclear estrogen receptors (ER) α and β are expressed in the majority of ovarian cancer [22][23][24]. Estrogens can be formed from the inactive steroid precursor estrone sulfate (E1-S) by the steroid sulfatase (STS) enzyme or from dehydroepiandrosterone sulfate (DHEA-S) or androstenedione by the aromatase (CYP19A1) enzyme [25]. An interesting study by Pavlic and colleagues reported a high steroid sulfatase expression and weak CYP19A1 expression in OVSAHO, Kuramochi, COV632 (three HGSOC cell lines) compared to immortalized normal ovarian epithelial HIO-80 cells, indicating that these cells produce estrogens from the precursor estrone sulfate (E1-S).…”
Section: Introductionmentioning
confidence: 99%